Re-dimensioning of a warehouse layout: a practical case - Madureira, Marlene (2020)
This study aims to design a new warehouse layout as a solution to the warehouse’s main problem: lack of space to store all the materials in stock. Besides the existing warehouse building, which currently presents an unsuitable layout for the storage of large volumes, there is a second area right next to the first to increase the storage area. The two buildings were re-dimensioned to accommodate a great quantity of stock, enabling one to transform the warehouse building into an industrial warehouse with appropriate storage methods. The final layout increased the storage area by 64%, from a total of 1.471,41 m2 to 2.414,22 m2 overall.